Concurrent chronic kidney disease in patients with inflammatory bowel disease, a systematic review and meta-analysis - Han, Xiaoping; Xu, Zifeng; Chang, Yu; Li, Hongyan; Hu, Sileng; Chang, Shiyu; Liu, Yue; Yu, Chanjiao; Tang, Tongyu; Li, Yuqin (Frontiers in Medicine, 2024)
Introduction Inflammatory bowel disease (IBD) is a multi-organ autoimmune disease that commonly affects the gastrointestinal tract, but can also affect other organs throughout the body. Less is known, however, about kidney involvement in IBD. Although IBD has been associated with chronic kidney disease (CKD) and end-stage renal disease (ESRD), these results have been inconsistent. The present study analyzed the prevalence of concurrent CKD and ESRD in patients with IBD. Methods PubMed, Cochrane, Web of Science, and Embase were searched for studies published through October 2023 on IBD patients with concurrent CKD or ESRD. Outcomes included the incidence rates and odds ratios (OR) of concurrent CKD and ESRD in IBD patients. The quality of included studies was assessed using the Newcastle-Ottawa Scale, and sequential sensitivity was analyzed. Publication bias was evaluated using Egger’s test. Results Nine studies were included in this meta-analysis. The combined results of eight studies, which included 239,042 IBD patients, showed that the prevalence of CKD in IBD patients was 5% (95% confidence interval [CI]: 1–9%). The combined results of two studies, which included 40,341 IBD patients, showed that the prevalence of ESRD in IBD patients was 0.2% (95% CI: −0.08–0.12%). The combined results of six case–control studies reported that the risk of CKD was significantly higher in patients with than without IBD (OR 1.36, 95% CI: 1.08–1.70, p = 0.008). Conclusion Although studies have shown an increased risk of CKD in IBD, due to the small number of included studies and high heterogeneity across studies, it is not enough to definitively conclude that CKD is more common in patients with IBD. But patients with IBD should be regularly monitored for CKD. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/.